Analysis of neutron induced reaction cross-section on 121,123Sb isotopes at neutron energy of 14.96 ± 0.03 MeV - Sharma, Shivani; Vandana; Bangotra, Pargin; Singh, N L; Mehta, Mayur; Singh, R K; Makwana, R J; Abhangi, Mitul; Kumar, Ratnesh; Sharma, Himanshu; Vala, Sudhirsinh; Katovsky, K (Applied radiation and isotopes, 2025)
The cross-section measurement of Antimony (Sb) is pivotal to modify or stagnate the rate of neutron flux in nuclear reactors. Neutron induced reaction cross-section data for isotopes of Sb is meagre as per reported in EXFOR. A comprehensive attempt has been made to analyse the reaction cross-section of 121Sb and 123Sb at monoenergetic neutron energy of 14.96 ± 0.03 MeV. The experiment was performed at the Neutron and Ion Irradiation Facility, Institute for Plasma Research (IPR), Gujarat (India). The 27Al(n,α)24Na reaction is used to monitor the flux and to estimate the cross-section of (n,2n), (n,p) reactions using neutron activation technique. Monoenergetic neutrons generated by D-T fusion reaction were bombarded on the natural sample of Sb to induce radioactivity. A High Purity Germanium detector (HPGe) with a resolution of 2.1 keV at 1.33 MeV γ-ray energy of 60Co based on GENIE software was used for the counting of emitted gamma photo peaks. Calculated results are compared with the existing studies from EXFOR. The cross-section values are estimated using TALYS-2.0 statistical code by employing different input parameters, along with the latest Evaluated Nuclear data libraries (ENDF/B-VIII.0, JEFF-3.3). To obtain more precise data, uncertainties from various parameters are propagated using the correlation coefficients among all the parameters. This systematic detailed covariance analysis helps to reduce the present discrepancies and to refine the nuclear data.